Hodnocení finanční pozice a výkonnosti podnikatelského subjektu a návrhy na její zlepšení - Němčík, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce se zabývá hodnocením finanční situace podniku Nástrojárna MM, s.r.o. Cílem práce je posoudit finanční situaci podniku za pomoci metod finanční analýzy, na jejichž základě jsou odhaleny nedostatky a navrhnuta opatření ke zlepšení finanční stability společnosti.

This bachelor’s thesis deals with the evaluation of a financial situation of the company Nástrojárna MM, s.r.o. The aim of the work is not only to evaluate company financial situation based on the results of financial analysis, but also to find weaknesses and to suggest ways how to improve financial situation that will lead to company financial stability.
Evaluation of Financial Position and Performance of Business Entity and Project of the Improvements
Keywords: Finanční analýza; SWOT analýza; rozvaha; výkaz zisku a ztrát; cash flow; horizontální analýza; vertikální analýza; rozdílové ukazatele; likvidita; rentabilita; poměrové ukazatele.; Financial analysis; SWOT analysis; balance sheet; profit and loss account; cash flow; horizontal analysis; vertical analysis; differential indicators; liquidity; profitability; financial ratios.